Mechanism of highly improved electrical properties in polypropylene by chemical modification of grafting maleic anhydride. (14th September 2016) - Zhou, Yao; Hu, Jun; Dang, Bin; He, Jinliang
Abstract: This paper reports excellent electrical properties in polypropylene grafted with maleic anhydride (PP-g-MAH) and a related mechanism of the enhanced electrical properties. The chemical structure of PP-g-MAH was analyzed and its effect on space charge accumulation, electrical breakdown strength and DC conductivity was studied. Compared with pure PP, the PP-g-MAH exhibits remarkably suppressed space charge accumulation, enhanced electrical breakdown strength and reduced conduction current. The mechanism enhancing the electrical properties was studied by measuring the trap level distribution. It can be explained that abundant deep traps are introduced in PP-g-MAH with the introduction of polar groups in MAH, which reduces the charge mobility and raises the charge injection barrier so as to suppress space charge accumulation. This investigation would contribute to propose a new material modification strategy for designing high-voltage direct current insulation material in addition to the inclusion of nanoparticles.